2017
DOI: 10.1088/1361-6560/aa5251
|View full text |Cite
|
Sign up to set email alerts
|

Time constants for temperature elevation in human models exposed to dipole antennas and beams in the frequency range from 1 to 30 GHz

Abstract: This study computes the time constants of the temperature elevations in human head and body models exposed to simulated radiation from dipole antennas, electromagnetic beams, and plane waves. The frequency range considered is from 1 to 30 GHz. The specific absorption rate distributions in the human models are first computed using the finite-difference time-domain method for the electromagnetics. The temperature elevation is then calculated by solving the bioheat transfer equation. The computational results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…An additional relaxation time accommodating the phase lag of the temperature gradient is analytically studied. Morimoto et al [21] studied the time constants of the temperature elevations in human head and body models exposed to simulated radiation from dipole antennas, electromagnetic beams, and plane waves within frequency range considered to be from 1 to 30 GHz. Tang et al discussed the thermal and vibrational characterization of human skin to find suitable and reproducible biomarkers for further clinical studies on intrinsic and extrinsic aging of dermis [22].…”
Section: Introductionmentioning
confidence: 99%
“…An additional relaxation time accommodating the phase lag of the temperature gradient is analytically studied. Morimoto et al [21] studied the time constants of the temperature elevations in human head and body models exposed to simulated radiation from dipole antennas, electromagnetic beams, and plane waves within frequency range considered to be from 1 to 30 GHz. Tang et al discussed the thermal and vibrational characterization of human skin to find suitable and reproducible biomarkers for further clinical studies on intrinsic and extrinsic aging of dermis [22].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal time constant has not been discussed until recently [23], except for a few studies on the exposure from handset antennas [20,21,22,23]. Instead, thermal damage in animal studies has been commented on in the international guidelines/standards.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on each condition, the thermal time constant can be expected to saturate as the effective SAR volume increases. The increment of the effective SAR volume results in thermal diffusion, causing the delay in temperature elevation [23]. This result suggests that the effective SAR volume can be estimated as a metric in superficial tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above calculations, we used a value of 500 s [Foster et al, ], as suggested by the newly approved standard [IEEE, ]. However, for local exposure, this time constant may take values as small as 100 s [Morimoto et al, ], resulting in a roughly twofold increase of the maximum temperature increase of the same pulse width.…”
Section: Thermal Time Constantmentioning
confidence: 99%